1995
DOI: 10.1111/j.1365-2591.1995.tb00167.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of ultrasound in removing intraradicular posts

Abstract: Thirty single-rooted teeth were prepared to receive cast posts. After cementation of the post the teeth were divided into three groups. Group I did not receive any treatment, whereas the posts in groups II and III were treated with an ultrasonic device, for 2 min and 5 min, respectively. The force required for post removal was determined using a universal test machine. No statistical differences (P > 0.05) were found between the groups where ultrasound had been used. Significantly reduced forces were necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…This is needed to flare the walls of a troughing groove in an axial direction. difficulties of removing posts without weakening, perforating, or fracturing the remaining root structure (85)(86)(87)(88). Many techniques and instruments have been described to aid in the removal of posts (52, 85, 88 -94).…”
Section: Root Canal Postsmentioning
confidence: 99%
“…This is needed to flare the walls of a troughing groove in an axial direction. difficulties of removing posts without weakening, perforating, or fracturing the remaining root structure (85)(86)(87)(88). Many techniques and instruments have been described to aid in the removal of posts (52, 85, 88 -94).…”
Section: Root Canal Postsmentioning
confidence: 99%
“…5,6,9 Although these methods can be used for evaluating the remaining retention of a cemented dental post, how to evaluate the post stability condition before the operation of post removal is still a question for dentists. In this study, we found that using NF value to represent the retention of a ZPC-cemented post is a possible solution.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis formulated in this study was confirmed: the shape of coronal cast dowel influenced the tensile strength necessary to remove it from the root canal. Ultrasound is a safe and efficient technique for intra‐radicular dowel removal with minimal wear of dental structure, avoiding perforation and minimizing fracture risk, and applicable to all teeth, including posterior teeth (2, 7–16). The ultrasonic oscillations are transmitted through the dowel with object of fracturing the cement seal, interposed between the dowel and the root canal walls, thus facilitating removal (14, 20).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is a safe and efficient technique for intra‐radicular dowel removal with minimal wear of dental structure, avoiding perforation and minimizing fracture risk, and applicable to all teeth, including posterior teeth (2, 7–16). The ultrasonic oscillations are transmitted through the dowel with object of fracturing the cement seal, interposed between the dowel and the root canal walls, thus facilitating removal (14, 20). For the without coronal anatomy reproduced groups, the results of this study showed that the force required for removing the custom cast dowel and core was small in the ultrasonically treated group, with statistically significant differences when compared with the control groups in which ultrasound was not used.…”
Section: Discussionmentioning
confidence: 99%